Results and Comparison of Volatility Between Prices Between IHSG And ISSI: A Case Study of The Turmoil Period 2020-2021 - Arie Sulistyawan; Muhamad Aji Purwanto; Imam Mahmudi (Bertuah Jurnal Syariah dan Ekonomi Islam, 2023)
Knowing the results and comparing the effect of the period of turmoil between the volatility of the Composite Stock Price Index(IHSG) and the Indonesian Sharia Stock Index (ISSI) is the purpose of this study.Then to compare the effect of the volatility of the IHSG and ISSI and find out the results of macroeconomic variables that show a period of turmoil in 2020 to 2021.The Covid-19 pandemic, the trade war between the United States and China, demonstrations against the Draft Law.  Job Creation with Gross Domestic Product (GDP), interest rates, world oil prices, inflation, rupiah-dollar exchange rates, interest rates, world oil prices, Shanghai Stock Exchange (SSE) Composite Index, and New York. The Stock Exchange (NYSE) is a time of turmoil inthis research.Five working days data from 2020 to 2021 which is used as a variable. Quantitative analysis usesTGARCH Model and VECM in this analysis method.Against the times of turmoil, Based on the results of TGARCHshows that ISSI volatility has a significant effectsmaller.Compared to volatility IHSG, According to the results of VECM analysisshows that the period of turmoil from 2020 to 2021 has more of an impact on ISSI's volatility.